Fecal Shedding, Antimicrobial Resistance and In Vitro Biofilm formation on Simulated Gallstones by Salmonella Typhi Isolated from Typhoid Cases and Asymptomatic Carriers in Nairobi, Kenya - Peter Muturi; Peter Wachira; Maina Wagacha; Cecilia Mbae; Susan Kavai; Musa Muhammed; John S. Gunn*; Samuel Kariuki* (International Journal of Clinical Microbiology, 2024)
Typhoid fever, caused by the human restricted pathogen Salmonella Typhi, remains a major global public health concern. Even after successful treatment, approximately 3-5% of patients with typhoid fail to clear the bacteria within one year and become chronic carriers. Most typhoid carriers have gallstones in their gallbladder, and biofilm formation on gallstones is highly correlated with chronic carriage. This study’s goal was to identify asymptomatic typhoid carriers in an endemic setting in Kenya, and to compare acute versus chronic isolates. A cohort of typhoid fever patients identified through blood and/or stool culture, and their household contacts, were followed up after treatment to detect longitudinal S. Typhi stool shedding. An abdominal ultrasound scan was used to identify individuals with gallstones. A total of 32 index patients and 32 household contacts were successfully followed-up. Gallstones were detected in 4 cases and 1 household contact. The duration of S. Typhi shedding was significantly longer in individuals with gallstones compared to those without, P<0.001. Eighty-three (83) S. Typhi strains were tested for susceptibility to commonly used antimicrobials and examined by in vitro biofilm formation assays. Out of 37 infected individuals, 32.4% had infections caused by multidrug resistant (MDR) S. Typhi strains and only 18.9% were infected by susceptible strains. Non-MDR strains formed significantly better biofilms in vitro than the MDR strains (P<0.001). This study provides data on S. Typhi chronic carriage that will influence public health approaches aimed at reducing typhoid transmission and the burden of infection.
Keywords: Salmonella